Implementación de herramientas psicoterapéuticas para el fortalecimiento de autorregulación emocional en niños de 7 a 14 años hijos de usuarias del centro de equidad y justicia de Tumbaco en el periodo de abril a junio del 2018. - Díaz Flores, Nicole Gabriela (2018)
The following work is a systematization of the implementation of the intervention project carried out with children and adolescents from 7 to 14 years old, children of users of the Tumbaco Equity and Justice Center, for the strengthening of emotional self-regulation during the period of April to June 2018. The aim was to provide psychotherapeutic tools, through techniques and tools of cognitive-behavioral rational therapy (TREC). Therefore, this intervention project focuses on working from a model that focusses not only the emotional sphere, but also the cognitive and behavioral sphere, because some problems detected in the children and adolescents, revolves around these three spheres. Therefore, working from this model is better, since it begins to recognize with what systems of thought each child and adolescent arrives and through exercises what we resignify these ideas, in order to generate changes in the emotional and cognitive levels.